Detection of Incidental Esophageal Cancers on Chest CT by Deep Learning - Sui, He; Ma, Ruhang; Liu, Lin; Gao, Yaozong; Zhang, Wenhai; Mo, Zhanhao (Frontiers in Oncology, 2021)
Objective: To develop a deep learning-based model using esophageal thickness to detect esophageal cancer from unenhanced chest CT images. Methods: We retrospectively identified 141 patients with esophageal cancer and 273 patients negative for esophageal cancer (at the time of imaging) for model training. Unenhanced chest CT images were collected and used to build a convolutional neural network (CNN) model for diagnosing esophageal cancer. The CNN is a VB-Net segmentation network that segments the esophagus and automatically quantifies the thickness of esophageal wall and detect positions of esophageal lesions. To validate this model, 52 false negatives and 48 normal cases were collected further as the second dataset. The average performance of three radiologists and that of the same radiologists aided by the model were compared. Results: The sensitivity and specificity of the esophageal cancer detection model were 88.8% and 90.9%, respectively for the validation dataset set. Of the 52 missed esophageal cancer cases and the 48 normal cases, the sensitivity, specificity, and accuracy of the deep learning esophageal cancer detection model were 69%, 61% and 65%, respectively. The radiologists’ independent results had a sensitivity of 25%, 31% and 27%, specificity of 78%, 75% and 75%, and accuracy of 53%, 54% and 53%. With the aid of the model, the radiologists' results were improved to a sensitivity of 77%, 81% and 75%, specificity of 75%, 74% and 74% and accuracy of 76%, 77% and 75%, respectively. Conclusions: Deep learning-based model can effectively detect esophageal cancer in unenhanced chest CT scans to improve the incidental detection of esophageal cancer.